2007
DOI: 10.7498/aps.56.2024
|View full text |Cite
|
Sign up to set email alerts
|

Study on the two-lane feedback controled car-following model

Abstract: In this paper we extend the single-lane feedback control model to the two-lane case, named as the two-lane optimal velocity feedback control (OVFC) model. Compared with the two-lane optimal velocity model, simulation results indicate that no serious traffic jams occur in the OVFC system when the feedback signal is introduced, and the oscillation of velocity becomes weaker or vanishes. This means that the two-lane OVFC model can suppress the traffic jams effectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Little attention has been paid to the control of traffic jams and the design of control systems for two-lane traffic flow from the viewpoint of control theory. However, recently, Chen et al [35] extended the single-lane feedback control model to the two-lane case and simulation results indicated that no serious traffic jams occur when the feedback signal is introduced, but they did not give the OV model for two-lane traffic flow and neglected the friction interference from the neighbouring lane. Moreover, when the lane changing behaviours are considered, the reason why the delayed feedback control method [33] was not chosen is that once a vehicle transfers to another lane, its past headway and lateral distance have no significance in the feedback adjustment of the vehicle motion.…”
Section: Introductionmentioning
confidence: 99%
“…Little attention has been paid to the control of traffic jams and the design of control systems for two-lane traffic flow from the viewpoint of control theory. However, recently, Chen et al [35] extended the single-lane feedback control model to the two-lane case and simulation results indicated that no serious traffic jams occur when the feedback signal is introduced, but they did not give the OV model for two-lane traffic flow and neglected the friction interference from the neighbouring lane. Moreover, when the lane changing behaviours are considered, the reason why the delayed feedback control method [33] was not chosen is that once a vehicle transfers to another lane, its past headway and lateral distance have no significance in the feedback adjustment of the vehicle motion.…”
Section: Introductionmentioning
confidence: 99%
“…Combining with the fundamental law of traffic flow (Q = ρυ), and discretizing the time variable in Eqs. (7) and (8), we obtain…”
Section: Modelsmentioning
confidence: 99%
“…However, when the headway of the considered car is larger than the safe headway, its driver adjusts the velocity according to the information about velocity difference to keep up with the leading one, and does not need to consider the safe headway effect. Therefore, a new feedback control signal u i (n) is designated as follows: (16) 090205-2 where 0 < k < 1 is the feedback gain, η is the safe headway, the function H(•) is described by…”
Section: Control Schemementioning
confidence: 99%
“…In 2006, Zhao and Gao [15] presented a simple strategy for congested traffic induced by bottlenecks in the traffic system. After that, many important achievements related to the control scheme [16][17][18][19][20][21][22] have been obtained.…”
Section: Introductionmentioning
confidence: 99%